Διερεύνηση του βαθμού ενημέρωσης και εφαρμογής οδηγιών της Ευρωπαϊκής Ένωσης και προτύπων στο τομέα της Μηχανικής στην Κύπρο - Κλεάνθους, Μάρκος (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
Purpose The main aim of this dissertation is the investigation of the importance of standardization as a concept and a science, the relevant directives of the European Union as well as the standards in general. Furthermore this paper attempts to examine the extend these are being implemented in engineering sector of Cyprus. Through a nationwide survey, the current situation in Cypriots was investigated according to the consumers in Cyprus own perspective and knowledge regarding the Cypriot businesses and institutions that are related in the field of mechanical engineering. Moreover the aim was to draw important conclusions which will lead to as a number of recommendations towards all possible levels of potential implementation for a more comprehensive and effective roll out of the knowledge/information acquired on the importance and the benefits of standardization. Methodology The study has drawn input from the research performed, interviews as well as an online tool for creating questionnaires. At the initial stage of the study, a historical background is laid out in the paper indicating the development and evolution of the standardization concept. The relevant terminology is thoroughly defined as a part of this study. The relevant stakeholders including both the different privately owned legal entities as well as the relevant public (government) services, that are operating in Cyprus, are presented in the study. Then, through interviews and a questionnaire the various companies and organizations, that were selected, were asked to provide their views on the possible, if any, benefits, possible improvements in processes on a financial level. Further to that the companies involved were asked to provide possible problems and disadvantages which they encountered from their experiences or maybe problems they foresee from a potential implementation of the standards, relevant directives etc. Based on the results of the research a comprehensive analysis was performed in regards to the identified pros and cons they were categorized, on one hand, as potential positive forces and opportunities of standards in business and on the other hand the possible failing and problems faced by the implementation of standards. At the final stage of the research, there were some important suggestions laid forward regarding the smooth penetration and finally the implementation of standards and guidelines-directives of EU in a business operating in Cyprus seeking to gain a competitive advantage in her market share. For a more complete and effective information of all interested members on the importance and benefits of standardization. The aim was to promote standardization as a tool of comparativeness for the Cypriot products and services. Results The results derived from the particular study have shown that the selected firms are well aware of the concept of standards and the fact that they have to implement them in their operations. Needless to say that a large percentage of companies are already implementing them and would recommend to other companies to incorporate them in their daily operations. It has been observed that most businesses are indeed purchasing standards regardless of the cost. Yet opinions vary, since other companies consider them expensive, other believes they are affordable but another percentage thinks that standards are expensive. Thoroughly examining the outcomes both of the interviews as well as the outcomes of the questionnaire, complemented by a SWOT analysis which indicates the strengths, weaknesses, opportunities and threads the following have been concluded. The implementation of standards, has enormously helped many businesses and managed to differentiate themselves from the rest, gaining that way a competitive advantage. Unfortunately nowadays, due to the economic crisis, it seems that some companies which have been negatively affected and they do not have the opportunity or they do not consider implementing standards as their priorities, since they are in a difficult position operating in the current adverse economic conditions of the market. Concluding, the benefits from implementing standards, in a company, will definitely provide several positive results. It would be of great importance if the accountable government services work towards a direction that will form a more favorable climate, maybe in the form of incentives, for the companies so that they proceed further with implementation of standardization, something that would undoubtedly benefit Cyprus as a whole.
Keywords: Standardization; European Union guidelines; Standards; Τυποποίηση; Οδηγίες Ευρωπαϊκής Ένωσης; Πρότυπα